An analysis of some variables of in-camera editing of anthropological video: a case study - Hayman, Graham Peter (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 1993)
Anthropological film and videomakers use their media for both research and education. In both cases, a formal technique of observational camerawork is required. In this thesis, appropriate continuity methods and a model of decision-making in camerawork are proposed, which are designed to deal with the certainties and uncertainties encountered in the observational type of ethnographic film. The ethnographic context of the research is the community in the Shixini area of the Transkei, where the author made video-recordings of a number of ritual and everyday events between 1981 and 1984. The model is tested on the case study of a "small event". There is an extensive amount of video material of a four-day mortuary ritual. The model is examined through a first-person account of the influences on decisions during shooting, and through formal analysis. Both of these examinations refer in detail to the unedited video material which accompanies the thesis, and assess how the decisions deal with time and space: with regard to the ritual markers and the continuity method. The thesis concludes that the model of camera work can be used to provide a coherent observation of the small event. The suitability of the model for editing is then tested. The unedited material of the case study is compared with an edited version. The ritual is represented in a narrative segment within a longer documentary, "Shixini December: Responses to Poverty in the Transkei". The complexity of editing operations is examined in detail by a variety of methods, and refers closely to the longer documentary. The fit between continuity in the unedited camera work and the edited version is established. A video copy of this documentary also accompanies the thesis. The unedited observational material is then tested for its use in research. An anthropologist screened the unedited material to ritual participants to elicit their responses, and with the results wrote a dissertation combining interpretation and ethnography. The detail of the ethnography and the consistency of the interpretation demonstrates the value of an observational video record. It does not conclusively demonstrate its validity for research, because the effect of video on memory needs further exploration. Instead of stimulating memory of off-camera action as may be expected, the video seems to anaesthetise it. Continuity methods can provide a clear but partial and fragmented observational record. This record has formal characteristics which are a necessary but not sufficient condition for editing into narrative. Continuity methods may provide a video record that is useful for research. If the video is used for reflexive validation, then a possible effect on the memory of off-camera events must be taken into account. The continuity characteristics of unedited video which result from in-camera editing can, but need not be, evident in subsequent texts based on them.
Keywords: Ethnology -- Methodology -- Case studies; Motion pictures in ethnology -- Case studies; Anthropology -- Study and teaching -- Audio-visual aids -- Case studies; Video tapes -- Editing -- Case studies